Cooked [compact disc, unabridged] : a natural history of transformation - Pollan, Michael (Penguin Audio, 2013)
"In Cooked, Michael Pollan explores the previously uncharted territory of his own kitchen. Here, he discovers the enduring power of the four classical elements-- fire, water, air, and earth-- to transform the stuff of nature into delicious things to eat and drink. Apprenticing himself to a succession of culinary masters, Pollan learns how to grill with fire, cook with liquid, bake bread, and ferment everything from cheese to beer. In the course of his journey, he discovers that the cook occupies a special place in the world, standing squarely between nature and culture. Both realms are transformed by cooking, and so, in the process, is the cook" -- from publisher's web site.